Pelayanan kesehatan di wilayah terpencil Buru Selatan, Maluku - Asmin, Elpira; Tahitu, Ritha; Yunita, Melda; Mainase, Josepina; Hataul, Is Asma’ul Haq; Mus, Rosdiana; Ramla, Razita; Nahumarury, Salmin; Hasibuan, Andrian Bayo Arif; Metekohy, Meilani (Jurnal PADE: Pengabdian & Edukasi, 2025)
The prevalence of non-communicable diseases in South Buru Regency is in the high category in the Maluku Province. Based on the 2018 Riskesdas data, the prevalence of non-communicable diseases in South Buru that have been diagnosed by doctors are diabetes mellitus (0.09%), heart disease (2.07%), hypertension (24.46%), stroke (9.2%) and joint disease (7.15%). The prevalence data for DM is 0.09% of the 382 residents examined, higher than Ambon City 1.93% of the 3,329 residents. Another thing that was found was that only 0.95% had ever been diagnosed with hypertension by a doctor in South Buru Regency. This community service activity aims to conduct screening as an initial step in early case detection and patient education. This activity was carried out in Waesama District, South Buru Regency. The activities in the form of health checks include anthropometric measurements, blood pressure, blood sugar levels and cholesterol. The results of the examination activities obtained that most participants had hypertension, almost half of the participants had high cholesterol. The conclusion was that many new cases of hypertension and cholesterol were found. Participants of the activity were given education during consultations with doctors and they were recommended to health facilities to check their health regularly.Keywords:  Hypertension, disease, health check